'It makes life worthwhile!' Peer mentoring in long-term care—a feasibility study. (3rd October 2021) - Theurer, Kristine A.; Stone, Robyn I.; Suto, Melinda J.; Timonen, Virpi; Brown, Susan G.; Mortenson, W. Ben
Abstract: Objectives: Loneliness and depression are of increasing concern in long-term care homes made more urgent by viral outbreak isolation protocols. An innovative program called Java Mentorship was developed that engaged community volunteers and resident volunteers (mentors) as a team. The team met weekly, received education, and provided visits and guidance in pairs to socially disengaged residents (mentees). The purpose of this study was to assess the feasibility of conducting a larger study. Method: We conducted a mixed-methods pre-post study to evaluate the program. We collected feasibility data associated with the program implementation, including assessment of the sample and ability to recruit; procedures for data collection; retention, program adherence and acceptability; and residents' responses including loneliness, depression, purpose in life, social identity and sense of belonging outcomes. We enrolled community mentors ( n = 65), resident mentors ( n = 48) staff facilitators ( n = 24) and mentees ( n = 74) in 10 Canadian sites. Results: Most feasibility objectives were met, and adherence and acceptability were high. Some resource challenges and low retention rates among resident mentors were noted. We found a 29% reduction in depression scores ( p = .048; d = .30) and 15% reduction in loneliness scores ( p = .014; d = .23). Purpose in life, social identity and sense of belonging were unchanged. Interviews among participants indicated high acceptability and positive perceptions of the program. Conclusion: The study findings reveal a potential role for mentorship as a viable approach to reducing loneliness and depression in long-term care settings and lay the groundwork for future research.